A fast spatial domain method for the suppression of excitation-induced spurious modes in SCN-TLM - Lindenmeier, Stefan; Isele, Bertram; Weigel, Robert; Russer, Peter (IEEE MTT-S International Microwave Symposium Digest, 1996)
A fast method for the suppression of excitation-induced spurious modes in the Transmission Line Matrix (TLM) method is presented for the symmetrical condensed node (SCN) scheme. The method of spurious-free excitation allows for a coarser mesh discretization improving the effectiveness of the TLM-simulation. The capability of the method is demonstrated by way of an example.
elib2cris::1512001600,lindenmeier1996